1983
DOI: 10.1126/science.6337399
|View full text |Cite
|
Sign up to set email alerts
|

[ 123 I]Insulin Metabolism in Normal Rats and Humans: External Detection by a Scintillation Camera

Abstract: [123I]Insulin was injected intravenously into rats and the distribution and kinetics of radioactivity were analyzed by external detection with a scintillation camera connected to a computer. When injected alone, [123I]insulin was rapidly taken up by the liver and to a smaller extent by the kidneys. After reaching a maximum at 3 to 5 minutes after injection, liver radioactivity rapidly declined and free iodide appeared in the plasma. After previous saturation of the insulin receptor compartment, [123I]insulin w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
33
0

Year Published

1984
1984
2005
2005

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 11 publications
(4 reference statements)
5
33
0
Order By: Relevance
“…In previous studies, we showed that the most prominent uptake occurred by the liver, which reached a maximum in 3-4 min and was about 30% of the total injected dose. This uptake appears to be receptor-mediated and can be blocked by injection of excess unlabelled insulin [14] or by antibodies to the insulin receptor [18]. Renal uptake represented about 15% of the total injected dose, but did not appear to be receptor mediated, and actually increased when hepatic uptake was blocked by insulin or anti-receptor antibody [14,18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies, we showed that the most prominent uptake occurred by the liver, which reached a maximum in 3-4 min and was about 30% of the total injected dose. This uptake appears to be receptor-mediated and can be blocked by injection of excess unlabelled insulin [14] or by antibodies to the insulin receptor [18]. Renal uptake represented about 15% of the total injected dose, but did not appear to be receptor mediated, and actually increased when hepatic uptake was blocked by insulin or anti-receptor antibody [14,18].…”
Section: Discussionmentioning
confidence: 99%
“…This uptake appears to be receptor-mediated and can be blocked by injection of excess unlabelled insulin [14] or by antibodies to the insulin receptor [18]. Renal uptake represented about 15% of the total injected dose, but did not appear to be receptor mediated, and actually increased when hepatic uptake was blocked by insulin or anti-receptor antibody [14,18]. In the present study, we have applied this technique to study insulin biokinetics and receptor interaction in the Zucker obese rat.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Insulin metabolism occurs mainly in the liver and, to a much lesser extent, in the kidneys and muscle tissues. The enzyme insulin-glutathione transhydrogense cleaves the intermolecular disulfide bonds holding the A and B chains.…”
Section: Diabetes Management and Anti-diabetic Drugs Classificationmentioning
confidence: 99%
“…3871-3876 , 1995 ) From plasma la bel deca y cu rves and in sulin con centrations , the in-C IRCULATING insulin has, nec essarily, a shor t ha lf-life (1), becau se of its fast respon se to hyp erglycem ic cha l lenges (2), a conseque nce of its funda me n tal ro le in the ma in tenance of gly cemia (3). The insulin resp onse to increases in circulating glucago n (4), ca techo lami nes (5), or amino acids (6)(7)(8) is pr actically immediate.…”
mentioning
confidence: 99%